Avaliação de cenários hidroagrícolas em sistemas de produção de base familiar na região do Extremo Oeste Catarinense - Guadagnin, Clístenes Antônio (2013)
The family-based agriculture in the Western region of Santa Catarina State is characterized by a diversity of integrated crop-livestock systems, combining different uses and managements in a complex set of soil types. These systems can changes in their physical and hydrological properties and influence its physical qualities, including the capacity to storage of water available to crops. In the studied region, periods of water deficiencies frequently reduce the productivity of maize, the crop of major socioeconomic importance. This study complies a priority demand set in 2009 by Epagri UGT9 in the field of water resources management, focusing methods of catchment, storage and use of water in agriculture. Our goals were to analyze the changes in the soil's physical and hydrological properties in several production systems and the effects of water limitation on maize production. We analyzed the effect of land uses and management in the commonest soil types and on the readily available water storage and estimated the reduction in productivity due to water limitation in simulations, considering different seeding seasons. We conducted the research in 36 family-based properties in the West region of Santa Catarina State. We collected soil samples of three classes, in three land uses and management types, four properties and four soil layers (0-0.10, 0.10-0.20, 0.20-0.40 e 0.40-0.60 m), totaling 144 samples, following a factorial design. We used the software ISAREG to calculate the water balance according to the Penman-Monteith/FAO methodology and estimated the loss of maize productivity for the seasons 1989/90 to 2010/11, simulating 19 different seeding dates and three different maturation cycles. We concluded that (1) the changes in the soil's physical and hydrological properties due to the land uses and management didn't impair the physical quality of the soils in the region; (2) the managements of minimum tillage, direct seeding and permanent pastures didn't affected the readily available water storage; (3) that, otherwise, the variations in water storage were influenced by the soil classes; (4) the mean content of readily available water storage was 31.4 and 49.6% higher in Cambissoils, comparing respectively with Latossoils and Nitossoils in the minimum tillage system; (5) the ISAREG model estimated a mean reduction of maize productivity of 25.1%; (6) the highest loss was for August seeding and the lowest for seeding in January and February, varying up to 3.9% among maturation cycles evaluated; (7) the ISAREG model was appropriate to estimate the loss in productivity, but overestimates the loss when Etr / Etc-1 rate is greater than 0.8; (8) there is a 50% probability of maize productivity losses of 25% in the evaluated seasons for the western region of Santa Catarina.